Steadfastness of Faith "Thematic Tafsir of QS Ali Imran" - Hakim, Qois Abdul; Rha'in , Ainur (Jurnal Indonesia Sosial Sains, 2025)
This study addresses the challenge of understanding and applying steadfastness of faith as expressed in QS Ali Imran verses 102-104 within contemporary Muslim life, bridging classical exegesis with modern realities. Given the pressures of globalization, cultural shifts, and technological changes, strengthening spiritual resilience is urgently needed to maintain social cohesion and personal faith. Prior research has explored aspects of faith, prayer, and cultural integration but lacks a comprehensive thematic approach that connects these teachings to current challenges. This study’s novelty lies in synthesizing classical and modern hermeneutics to provide a holistic framework emphasizing patience, sincerity, and reliance on God, making the Qur’anic message practically relevant today. Using thematic interpretation, the research aims to deepen understanding of faith’s role in fostering resilience and unity. The findings offer valuable guidance for Muslims, educators, and scholars, supporting spiritual steadfastness and social solidarity amidst modern trials, thereby contributing meaningfully to Islamic scholarship and community well-being.